SIFAT PASTA PATI MILLET (Pennisetum glaucum (L.) R. Br.) TERMODIFIKASI HEAT MOISTURE TREATMENT UNTUK PEMBUATAN SOHUN - Retno Widyastuti (AGRISAINTIFIKA: Jurnal Ilmu-Ilmu Pertanian, 2021)
Improve the consumption of millet to vermicelli promoted for food diversification. Millet starch less stable of stirring and heating. Starch modification can improve the quality. In this research to evaluate pasting character of millet starch modified by heat moisture treatment which suitable for vermicelli. Heat moisture treatment conditioned at 25% moisture content and heating 100, 130 and 150 0C for 3, 5 and 7 hours with oven. Crystalline and starch paste properties of modified starch were analyzed and then selected to vermicelli. The suitable starch for vermicelli which stable paste of stirring and heating and high gel strength. The results show modified starch with 100 °C for 7 hours has an ideal for vermicelli. Shown by lower peak viscosity and viscosity breakdown (2951 cP and 71 cP), high final viscosity (3695 cP).Keyword : Heat moisture treatment, millet starch, RVA, pasting properties